PENGARUH INTELLECTUAL CAPITAL DAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Sektor Consumer Cyclicals dan Non-Cyclicals di Bursa Efek Indonesia Tahun 2021-2024) - Salsabila Pramudita; Siti Mutmainah (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of Intellectual Capital (IC) and Capital Structure on Financial Performance with Good Corporate Governance (GCG) as a moderating variable. The research focuses on companies in the consumer cyclicals and consumer non-cyclicals sectors listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The study employs a quantitative method with a purposive sampling technique. Data were obtained from annual reports and financial statements published on the official IDX website. The independent variables consist of intellectual capital, measured using the Value Added Intellectual Coefficient (VAIC™) method, and capital structure, proxied by the Debt to Asset Ratio (DAR). The dependent variable, financial performance, is measured by Return on Assets (ROA), while Good Corporate Governance (GCG) is proxied by the proportion of independent commissioners and the existence of an audit committee as the moderating variable. Data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS software.The results indicate that intellectual capital has a positive and significant effect on financial performance, while capital structure has a negative and significant effect. Furthermore, Good Corporate Governance shows a significant moderating effect by weakening the relationship between intellectual capital and financial performance, and strengthening the negative influence of capital structure on financial performance. This suggests that a stricter implementation of GCG may limit managerial flexibility in managing intellectual resources and financing policies, thereby reducing the overall impact of these variables on financial performance.